Determination of the tectonic evolution from fractures, faults, and calcite twins on the southwestern margin of the Indochina Block - Francesco Arboit (2018)
©2015. American Geophysical Union. All Rights Reserved. In polyphase tectonic zones, integrating a study of fault and fracture with calcite twin analysis can determine the evolving paleostress magnitudes and principle stress directions that affected the area. This paper presents the results of the analyses of fractures, striated faults, and calcite twins collected within the Khao Khwang Fold-Thrust Belt in central Thailand (SE Asia). Here we attempt to reconstruct the orientation of the principal stresses that developed during the tectonic evolution of this highly deformed, polyphase orogen. Tectonic data were collected in the Permian carbonates of the Khao Khad Formation of the Saraburi Group, and five successive tectonic stages are determined that are interpreted to have developed before, during, and after, the Triassic Indosinian Orogeny. The first three stages predate the main deformation event: the first stage is interpreted as a pre-Indosinian N-S extensional stage, the second stage described a N-S strike-slip and compressional regime, largely perpendicular to the fold axes of the main structures, while the third stage is associated with an E-W compressional strike-slip phase. A further two stages took place after, or during, the main folding event and correspond to N-S compression and to an E-W composite strike-slip/contractional stage, the latter which is interpreted to represent Cenozoic deformation related to the India-Asia collision. Key Points Paleostres evolution of SE Asia Indosinian Orogeny Calcite twins-faults-fractures.